#TITLE_ALTERNATIVE# - Teja Harjaya (NIM 23496059), Immanuel
Abstrak : The purpose of this study is to investigate the hypothesis that trade liberalization policy may have positive impact to Total Factor Productivity (TFP) on Indonesia manufacturing industries during 1980 --1996. Firstly, this study computes TFP of Indonesia manufacturing industries using Malmquist productivity indexes model. This model decomposes the Malmquist productivity change index into technical change and technical efficiency. Secondly, this study concentrates on finding out the impact of some trade liberalization policy on growth of TFP in manufacturing industries by doing a regression analysis of various policies/variables (effective rate of protection, foreign investment, capital intensity and import of material input). Almost all productivity growth is due to technical change, and there are some evidence that over this period analysis we find out of falling productivity growth in almost all manufacturing sectors. We also find that the rate of productivity growth is very small near to zero, even some manufacturing sector have negative rate of productivity growth. The statistical results of defference between two means . for TFP reveal that there is not subsector showed a significant average increase but the trend over time shown that the rate of productivity growth decreases. As regards the regression analysis, the results show that all of the explanatory variables have negative impact on productivity growth or in the other word we reject all the null hypothesis.